Restoration of Property Rights over Destroyed Land: Comparative Legal Analysis of Indonesia and the Philippines - Adya Nurnisa; Retno Saraswati; Ana Silviana (Fakultas Hukum Universitas Muhammadiyah Sorong, 2026)
This study aims to identify and analyze a comparison of the models for restoring property rights over land affected by destruction implemented by Indonesia and the Philippines, with a view to improving the legal system governing destroyed land in Indonesia in the future. This study employs a doctrinal research method using statutory, conceptual, and comparative approaches. This study involves the collection and inventory of regulations regarding destroyed land in both Indonesia and the Philippines, followed by a descriptive analysis. The novelty of this study lies in the conclusion that Indonesia needs to adopt a legal certainty framework for destroyed land using a hybrid model namely, judicial reconstruction and administrative reconstruction The results of this study indicate that current regulations on lost land in Indonesia provide an opportunity for original titleholders to reclaim lost land within a one-year period; if they cannot prove ownership, it is not recognized as such. In contrast, unlike the Philippines, which uses a hybrid model to guarantee and recognize its citizens’ property rights through judicial and administrative reconstruction, provided they possess “legal title” registered with the Land Registration Authority. The conclusion of this study indicate that the current policy framework for land loss in Indonesia should take into account models for restoring property rights following land loss or damage that exist in other countries, such as the Philippines. This is to ensure that property rights